Social causes of health and disease - Cockerham, William C. (Cambridge, U. K. : Polity Press, 2013)
In this stimulating book, William C. Cockerham, a leading medical sociologist, assesses the evidence that social factors (such as stress, poverty, unhealthy lifestyles, and unpleasant living and work conditions) have direct causal effects on health and many diseases. This engaging text will be indispensable reading for all students and scholars of medical sociology, especially those with the courage to confront the possibility that society really does make people sick.
Includes bibliographical references (p. [208]-241) and indexes.
Keywords: Social medicine; Health -- Social aspects; Diseases -- Social aspects